Results of a Hepatitis C Virus Screening Program of the 1945–1965 Birth Cohort in a Large Emergency Department in New Jersey. (26th March 2018) - Cornett, Julia Kang; Bodiwala, Vimal; Razuk, Victor; Shukla, Devangi; Narayanan, Navaneeth
Abstract: Background: Persons born between 1945 and 1965 account for an estimated 81% of those infected with hepatitis C virus (HCV) in the United States. However, up to 60% remain undiagnosed. Prior studies have reported HCV screening results from large urban emergency departments. Methods: This is a retrospective cohort study of patients in the 1945–1965 birth cohort tested for HCV in a large emergency department (ED) in New Jersey from June 1, 2016, through December 31, 2016. The purpose was to report HCV antibody and viral load results of this testing program located in a small urban/suburban area and to analyze specific characteristics associated with positive results, such as race/ethnicity and insurance status. Descriptive statistics were performed, and, using a multivariate logistic regression model, adjusted odds ratios and 95% confidence intervals were calculated. Results: A total of 3046 patients were screened: 55.8% were white, and 17.9% were black; 52.1% had private insurance, 33.4% Medicare, 3.9% Medicaid. One hundred ninety-two were antibody positive (6.3%). Of 167 with HCV viral load testing results, 43% had a positive viral load. On multivariate analysis, black race and Medicaid were independently associated with a positive HCV viral load. Conclusions: HCV antibody seropositivity was above 6% and twice as high as the Centers for Disease Control and Prevention estimated prevalence in this birth cohort. These results indicate that EDs outside of large urban cities are also important sites for routine HCV screening. Other findings of interest include 43% with chronic HCV infection and the persistent association between black race and positive HCV viral load even when adjusted for insurance status.